Reparar as cores. Etnografia do cerrado junto às mulheres no sertão das veredas - Lima, Jacqueline Stefanny Ferraz de (2022)
This thesis presents an ethnography of the cerrado with the women who live in the sertão das veredas, geographically located in the northwest of Minas Gerais state (Brazil). Walking, knowing, and writing the cerrado together with the women's mexidas is the main task of this work. Its main argument follows the idea of reparar as cores [repairing the cerrado colors], an expression often used in the sertão das veredas that express the variety of forms found in the colors of the landscape. This thesis is attentive to the ordinary practice, to everyday relations among rural women and the contrasts between the poverty of development and the riqueza [wealth] in the cerrado. It is about the relation of time and the abundance that comes from the variety of collective practices of economic organization. Likewise, it focus on the nuances of the women's adherence to development projects, and the way they create difference and wealth, in contrast to the pecuniary quantification of the cerrado. It also discusses the various ways people establish prices in very particular economic transactions. Finally, it deals with the color of pigmentations that, in face of lived experiences amid the transformations of the land, the waters, the wind, the flowers, the landscape, paint an image against the secamento do tempo [the drying of time] in the cerrado.